Developing sustainable leadership - Davies, Brent, 1949- (Paul Chapman Pub. ; SAGE Publications, 2007)
'School leaders and teachers know a lot more than they think they do. So, what prevents the release of that creative energy? Look, no further than this thought provoking collection of essays from world leading scholars. It treats us to a kaleidoscopic view of what we do know, what we ought to know and what we urgently need to do to harness the power of sustainable leadership. Policy makers, please take careful note!'- John MacBeath, Professor Education Leadership, University of Cambridge. With increasing accountability pressures, developing and sustaining leaders is a major challenge for all t.